Analysis of GMO food products companies: financial risks and opportunities in the global agriculture industry. (2017) - Martin, Hannah M.; Durr, David; Smith, L. Murphy; Finke, Rachel; Cherry, Audie
One of the biggest issues facing the global agriculture industry is the use of genetically modified organisms (GMOs) in crops and food products. This study compares financial performance of major GMO food companies to other industries. Findings indicate that GMO companies had an average higher return on equity but also a higher level of risk. In addition, the study presents positive and negative perspectives toward GMO foods, along with a discussion of the risks and opportunities. Agricultural studies indicate that applying GMO technology is likely the most effective way to feed many of the world's hungry. In addition, research supports the safety and nutritional benefits of GMO food products. However, concerns expressed by GMO opponents have been effective in limiting GMO acceptance by the public. Research indicates that the inconsistency between negative public opinion and positive scientific evidence supporting GMO crops is at least partly the result of misrepresentations about GMOs. The ultimate acceptance or rejection of GMO foods will greatly affect food producers, distributors, retailers, and consumers.